Glutathione (GSH) and the GSH synthesis gene Gclm modulate plasma redox and vascular responses to acute diesel exhaust inhalation in mice. (28th June 2013) - Weldy, Chad S.; Luttrell, Ian P.; White, Collin C.; Morgan-Stevenson, Vicki; Cox, David P.; Carosino, Christopher M.; Larson, Timothy V.; Stewart, James A.; Kaufman, Joel D.; Kim, Francis; Chitaley, Kanchan; Kavanagh, Terrance J.
Abstract: Context : Inhalation of fine particulate matter (PM2.5 ) is associated with acute pulmonary inflammation and impairments in cardiovascular function. In many regions, PM2.5 is largely derived from diesel exhaust (DE), and these pathophysiological effects may be due in part to oxidative stress resulting from DE inhalation. The antioxidant glutathione (GSH) is important in limiting oxidative stress-induced vascular dysfunction. The rate-limiting enzyme in GSH synthesis is glutamate cysteine ligase and polymorphisms in its catalytic and modifier subunits (GCLC and GCLM) have been shown to influence vascular function and risk of myocardial infarction in humans. Objective : We hypothesized that compromised de novo synthesis of GSH in Gclm − /+ mice would result in increased sensitivity to DE-induced lung inflammation and vascular effects. Materials and methods : WT and Gclm − /+ mice were exposed to DE via inhalation (300 μg/m 3 ) for 6 h. Neutrophil influx into the lungs, plasma GSH redox potential, vascular reactivity of aortic rings and aortic nitric oxide (NO) were measured. Results : DE inhalation resulted in mild bronchoalveolar neutrophil influx in both genotypes. DE-induced effects on plasma GSH oxidation and acetylcholine (ACh)-relaxation of aortic rings were only observed in Gclm − /+ mice. Contrary to our hypothesis, DE exposure enhanced ACh-induced relaxation of aortic rings in Gclm − /+ mice. Discussion and conclusion : These data support the hypothesis that genetic determinants of antioxidant capacity influence the biological effects of acute inhalation of DE. However, the acute effects of DE on the vasculature may be dependent on the location and types of vessels involved. Polymorphisms in GSH synthesis genes are common in humans and further investigations into these potential gene-environment interactions are warranted.